2021
DOI: 10.1177/03611981211011642
|View full text |Cite
|
Sign up to set email alerts
|

Speeds of Right-Turning Vehicles at Signalized Intersections during Green or Yellow Phase

Abstract: The operation and design of signalized intersections involves tradeoffs between operational efficiency and safety for a variety of users, including motorists, pedestrians, and bicyclists. Additionally, the mix of vehicle types in the fleet sometimes requires special considerations. These concerns especially apply to the selection of curb radius at the corners, where right-turning vehicles operate close to pedestrians. Larger curb radii accommodate the swept paths of trucks and allow right turns to occur at hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Although corner radius is objective and easy to measure, the presence of shoulders, parking lanes, bike lanes, and multiple receiving lanes can all allow a driver to have a far wider turning radius than what a corner radius might imply. The authors indicate that the model was built on data from sites in Dallas, Bryan, and College Station, TX, where no bike or parking lanes were present on the approach or the receiving leg, all sites were at right-angle intersections, more than 90% had more than one receiving lane, and sites with complex curvature or a channelized turn island were excluded from the study ( 25 ). From drawing vehicle turning paths in AutoCAD for intersections with those conditions, we found that the turning radius was always about 31-ft greater than the corner radius.…”
Section: Recommended Model Parameter Values and Acceleration Profilementioning
confidence: 99%
“…Although corner radius is objective and easy to measure, the presence of shoulders, parking lanes, bike lanes, and multiple receiving lanes can all allow a driver to have a far wider turning radius than what a corner radius might imply. The authors indicate that the model was built on data from sites in Dallas, Bryan, and College Station, TX, where no bike or parking lanes were present on the approach or the receiving leg, all sites were at right-angle intersections, more than 90% had more than one receiving lane, and sites with complex curvature or a channelized turn island were excluded from the study ( 25 ). From drawing vehicle turning paths in AutoCAD for intersections with those conditions, we found that the turning radius was always about 31-ft greater than the corner radius.…”
Section: Recommended Model Parameter Values and Acceleration Profilementioning
confidence: 99%
“…For right-turn conflicts, corner radius categories (small, medium, large) are also considered as a proxy for turn speeds. This is because a large corner radius results in higher vehicle turning speeds, and recent research shows that, all else being equal, higher pedestrian crashes are expected at intersections with an increase in corner radius ( 12 ). Note that corner radius categories are used to make the calculation simple rather than requiring an analyst to the measure corner radius and estimate the associated turn speed.…”
Section: Performance Metrics Developmentmentioning
confidence: 99%
“…For turning vehicles, however, the tasks are complicated since the geographical trajectory planning and calculation should generate both speed/acceleration and turning angle profiles, which needs to determine the turning pattern and the turning radius first. In this stage, the variety in vehicle sizes [21], planning algorithms [22], intersection geometric property [23][24][25], and desired turning speeds [21,26,27] directly leads to different turning patterns and radiuses, referring to variation in both vehicle position and speed trajectories. In the trajectory tracking and maneuvering, the speed and turning angle are required to be adjusted simultaneously.…”
Section: Introductionmentioning
confidence: 99%